Angiostrongylosis clinical forum: a case presenting in a Terrier. Issue 7 (16th September 2013) - Maltman, Mark; Wray, Jon; Morgan, Eric; Andrews, Dan
<x xml:space="preserve">Abstract</x> Angiostrongylosis has emerged as a relatively common diagnosis in dogs in the UK over the past 10 to 15 years. The disease is caused by the nematode Angiostrongylus vasorum (commonly known as lungworm), whose life cycle includes a mollusc intermediate host. Disease presentation is very varied, including lung disease, coagulation defects, right‐sided heart failure and neurological disease. This forum presents a case of right‐sided heart failure secondary to pulmonary hypertension caused by A. vasorum, followed by a discussion on the diagnosis and treatment of the disease.